Telemedicine for Neurological Consultations in Nepal - Gajurel, Bikram; Tamrakar, Parishma (Nepal Journal of Neuroscience, 2022)
Introduction: Telemedicine is a method of using a variety of telecommunication techniques to evaluate patients. This research was carried out to study the clinical and demographic characteristics of the patients who sought neurological care via telemedicine during the first and second waves of the coronavirus disease 2019 pandemic. Methods and Materials: It is a retrospective study based on patients’ records. Patients were consulted via Viber, WhatsApp, Facebook Messenger and telehealth facility of Danphe Care. The data were entered into and analyzed by using the Statistical Package for the Social Sciences version 26. Results: A total of 197 patients were examined. Viber was the most common tool used (n=109, 55.3%). One hundred and twenty-two patients (61.9%) were from outside the Kathmandu Valley. Majority of the patients (n=155, 78.7%) did not come across any technical disturbances during the consultation. Cerebrovascular diseases were the most common diseases evaluated followed by headache disorders and seizures. One hundred and thirty-seven patients (69.5%) did not require further investigations, 179 (90.9%) did not require in-person evaluations and 142 (72.1%) did not require referral to other specialists for further evaluation. Majority (54.3%) of the patients became better at follow-up. All patients who became better had at least one follow-up compared to 82.2% of the combined who remained static or had unknown status of their health in follow up (p = <0.001). Conclusion: Telemedicine is a useful tool to evaluate various neurological disorders. Even though most of the patients did not require investigations, referrals and in-person visits, majority of the patients improved. Patients who have at least one follow-up became better compared to patients who did not have any follow-ups.